2013
DOI: 10.1097/pai.0b013e31827da412
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Prognostic Significance of Livin, Caspase-3, and Ki-67 in the Progression of Human Ampullary Carcinoma

Abstract: Livin is a new member of the inhibitor of apoptosis proteins family of proteins that interacts with downstream caspases, such as caspase-3, caspase-7, and caspase-9, however, its role in human ampullary carcinoma has not been clearly defined. Immunohistochemistry was used to evaluate tissue samples from patients with ampullary carcinomas (n=71) using antibodies against livin, Ki-67 (a proliferation marker), and caspase-3. Livin was detected in 33/71 cases (in the cytoplasm of all and in the nucleus of only 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Livin is recruited to death receptor signaling complexes, inhibits the activation of caspases responsible for apoptosis, and thereby protects cells from diverse proapoptotic stimuli. An increasing number of studies have demonstrated that the deregulation of livin is associated with tumor progression and poor prognoses in breast, bladder, and colorectal cancers . Livin and survivin are members of the IAP family, a group of antiapoptotic factors that play an important role in inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Livin is recruited to death receptor signaling complexes, inhibits the activation of caspases responsible for apoptosis, and thereby protects cells from diverse proapoptotic stimuli. An increasing number of studies have demonstrated that the deregulation of livin is associated with tumor progression and poor prognoses in breast, bladder, and colorectal cancers . Livin and survivin are members of the IAP family, a group of antiapoptotic factors that play an important role in inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that the deregulation of livin is associated with tumor progression and poor prognoses in breast, bladder, and colorectal cancers. [27][28][29][30][31] Livin and survivin are members of the IAP family, a group of antiapoptotic factors that play an important role in inhibiting apoptosis. The overexpression of IAPs is highly correlated with can-cer progression and resistance to chemotherapy and is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is encoded by the BIRC5 gene located on the chromosome 17q25 (44). Livin has been identified as a new member of the IAP family which was first identified in melanoma samples and was named melanoma inhibitor of apoptosis (45). Livin, a member of the inhibitors of apoptosis proteins, is overexpressed in tumor tissues and is detected at substantially lower levels or not expressed at all in corresponding normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…P21 mainly regulate the activity of intracellular CDK (cyclin dependent kinase) leaving the cells in the G1 or G2 phase (47)(48)(49), through the regulation of tumor suppressor gene p53, but also by p53-dependent manner by other factors induced by the production. Ki67 have been described as a reliable indicator in the rate of cell proliferation, which is a proliferation marker expression in cells expression throughout all stages except G0 phase (45).…”
Section: Discussionmentioning
confidence: 99%
“…High nuclear livin protein expression is found to predict satisfactory prognosis of renal cell carcinoma [19], and children with acute lymphoblastic leukemia positive for livin protein are reported to have a satisfactory prognosis [20]. However, it appears that high expression of the livin gene predicts poor prognosis of breast cancer [21], and high livin protein expression is reported to be associated with early-stage relapse of breast cancer and the lymph node metastasis of ampullary carcinoma [22, 23]. In addition, livin expression is found not to be associated with the prognosis of HCC [24], and the expression of the livin gene is reported not to be related to the survival period of patients with non-small-cell lung cancer [6].…”
Section: Discussionmentioning
confidence: 99%